Three Major Stages in the Historical Development of Translation - El-Mokhtar, Ahmed Mohamed Lemine (Journal of Humanities & Social Sciences, 2023)
Translation is about the transfer of a meaning or a cultural aspect from one language or culture to another. Translation has been participative in the development of international cultures. The main aim of translation is to facilitate communication between people from different socio-cultural backgrounds. Translators played pivotal roles to transmit ideas, social practices, customs and traditions between nations across the world. There are several stages, which marked the historical development of translation. Covering these stages equips translators with useful information they need during the process of translation. Translation started orally before the invention of writing and continued to develop after the advent of writing and the emergence of technology. Adopting a descriptive approach, this article contextualizes the historical emergence of translation as a means of bridging two or more cultures. It highlights three of the major stages marking the development of the field of translation. It includes three sections on oral translation, translation after the advent of writing and translating religious texts. It concludes that the first form of translation, oral or interpretation, remained a critical form of translation and maintained its popularity up to now in the era of advanced technology.